The Strategy for Implanting Character Values in Akidah Akhlak Subjects for Elementary Education Level Students - Fadli, Muhammad; Mukti, Abd.; Haidir, Haidir (Jurnal Basicedu, 2022)
This study aims to describe the strategy of inculcating character values in the subjects of moral aqidah for students of basic education level. This study uses a qualitative approach with descriptive analytical study method. The data collection techniques used were observation of learning activities in madrasas, then interviews with informants, and document studies. Data analysis uses data reduction techniques, as an effort to sort out the data needed according to relevance to the research theme, then the researcher presents the data to verification to draw a conclusion. Test the validity of the data using triangulation techniques. The results of this study concluded that (1) the character values contained in the aqidah morals lesson, the material of adab hanging out with relatives and friends and the story of the exemplary friend of Abu Bakar Ash-Siddiq ra. (2) the strategy applied by the teacher in instilling character is the internalization of values and habituation. (3) The most supportive factor in this activity is the teacher's strategy and approach to students, then other supporting factors also cannot be separated from a good playing environment and the most important support from parents. While the inhibiting factors are students who are less obedient to the rules that have been made, then the implementation time is not right, and the most important is parental support to participate in controlling their children at home and in their play environment.